Case Report: Fetal cardiac rhabdomyoma caused by TSC1 mutation - Feng, Xueqin; Ren, Qinnggui; Li, Haihong; Liu, Xinying; Li, Lijuan (Frontiers in Pediatrics, 2025)
Fetal rhabdomyoma is a rare benign cardiac tumor that primarily occurs during the fetal or neonatal period and is often associated with Tuberous Sclerosis Complex (TSC). It is most commonly found in the heart (particularly in the ventricles or interventricular septum) but can also occur in other locations such as the head and neck. It may be accompanied by arrhythmias (e.g., supraventricular tachycardia), pericardial effusion, or fetal hydrops. Larger tumors can lead to blood flow obstruction, heart failure, or sudden death. In this case, prenatal ultrasound at 22 weeks of gestation suggested a “possible fetal left ventricular rhabdomyoma” in the proband. The parents were advised to undergo prenatal diagnosis but declined and opted for induced labor. Whole-exome sequencing (familybased) revealed a heterozygous TSC1 mutation in the proband, while both parents exhibited wildtype genotypes. This case report presents an instance of fetal cardiac rhabdomyoma induced by a heterozygous TSC1 mutation, providing valuable insights for the early diagnosis and management of intrauterine fetal cardiac developmental abnormalities.